Impacto da adição de hidrogênio verde nas propriedades do gás natural em um sistema canalizado local - Torres, Lucas de Almada (2023)
Green hydrogen gas has been gaining prominence in the industrial area as it is considered a clean fuel that has the capacity to play an important role in the global energy transition. The addition of hydrogen to natural gas contains energy needed for industrial and residential applications to replace natural gas. Furthermore, it has lower CO2 emissions compared to natural gas. The present work aims to evaluate the injection of green hydrogen into the local natural gas network. Three (3) scenarios for the addition of hydrogen gas were evaluated: (i) scenario 1, consisted of adding hydrogen to a natural gas line; (ii) scenario 2, hydrogen was added to a biomethane line; (iii) scenario 3, hydrogen was added to a line mixed with natural gas and 15% biomethane. To evaluate the higher calorific value and the Wobbe index, the NBR 15213 standard was used, which specifies methods for calculating physicochemical properties. The Wobbe index is a measure of the energy content of a gas, measured based on its calorific value per unit volume at standard pressure and temperature, used as an indicator of burner interchangeability. The calculation method defined was that of real dry gases, for this method it is necessary to calculate the compressibility factor, which is also defined by the same standard. The measurement and reference conditions adopted for gas temperature and pressure are 20°C and 101.325kPa, respectively. To evaluate the methane number, ANP resolutions no. 16/2008 and no. 886/2022 were used. Scenario 3, referring to pure biomethane, presented as a restriction the addition of hydrogen to just 3%, limiting greater additions of hydrogen by specifying the higher calorific value. For scenario 1, natural gas is restricted to the addition of hydrogen at 11%. Greater additions of hydrogen are limited to the higher calorific value and number of methane. For the addition of hydrogen to a mixture of natural gas and biomethane, scenario 2, the restriction on the addition of hydrogen is 10%, limiting a greater addition of hydrogen by restricting the higher calorific value.